Seasonal change of soil precompression stress in coffee olantation under sub-humid tropical condition - Iori, Piero; Dias Junior, Moacir de Souza; Ajayi, Ayodele Ebenezer; Guimarães, Paulo Tácito Gontijo; Souza, Zélio Resende de; Figueiredo, Vanessa Castro (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to describe the seasonal change of precompression stress behavior in coffee plantations in the sub-humid tropic zone of Brazil as affected by agriculture traffic associated with the time since the establishment the coffee plantation, field slope, sampling position in and sampling depths. The coffee plantations on a uniform soil type; Red-Yellow Latosol were aged 2, 7, 18 and 33 years. Areas with side slope of 3, 9 and 15% were selected in these coffee plantations for this study. The soil was sampled at three positions on the coffee plantation row (bottom of traffic line, inter-row and top of traffic line) and at two depths (topsoil and sub-surface). Samples were collected over a one year period for each month of year. The study showed that the time since the establishment of a coffee farm and the slope steepness had significant effect on soil disturbance in mechanized operation. The coffee plantation with longer establishment time and on steeper terrain had higher precompression stress. The top traffic line presented higher load-bearing capacity than inter-row and bottom traffic line. The sites were more susceptible to compaction in the period from November to January of the year , because the Red-Yellow Latosol presented lower load-bearing capacity than the stress applied by tractor used in coffee management practices.